Right to Information: The Roles and Contributions of Information Professionals of Bangladesh - Hoq, Kazi Mostak Gausul (Philosophy and Progress, 2016)
With increasing recognition of information as a critical ingredient of development, the issue of right to information is gaining prominence quickly. Although Bangladesh parliament passed the Right to Information Act in 2009, larger cross-sections of people still suffer from an acute paucity of information because of lack of awareness and weak information infrastructure of the country. Globally, library and information professionals are making substantial contributions in the right to information campaign, but in Bangladesh, their role in this regard is quite negligible. The paper highlights the roles and possible contributions of library and information professionals of Bangladesh in ensuring right to information for common people. It underscores the dilemmas faced by the information professionals in this regard and indicates ways for information professionals to play a more dominant role in the campaign for right to information. Philosophy and Progress, Vol#53-54; No#1-2; Jan-Dec 2013